How important is entrepreneurial orientation for family businnes? - Visser, Thea (Array, 2020)
The purpose of this article is to explore how important is the entrepreneurial orientation for family businesses. Entrepreneurial orientation is an important concept within the entrepreneurship field and it should be maintained through family generations. Proactiveness, risk-taking and innovativeness form the essence of entrepreneurial orientation, while the generational level is an influential variable, related to entrepreneurial orientation. A preliminary and conceptual study of the described problem was undertaken. Although risk-taking is essential in developing entrepreneurship and sustaining the family legacy, family businesses are risk-averse, due to concerns about reduction in family wealth. Entrepreneurial orientation may be strong at the founder stage, but it decreases as the business moves through generations. Entrepreneurial families should have an entrepreneurial orientation towards business activities, as it provides the vision to mobilise the knowledge within the family business. Strong and consistent family leadership is needed to create a climate favouring entrepreneurial orientation. Families should develop an entrepreneurial spirit and orientation that can sustain the current generation and the entire family into the future.